The Influence of Digital Technology in the Transformation of Sociocultural Communication - Hawarini, Nopriyanti; Syobah, Sy. Nurul; Wijaya, Ida Suryani; Effendi, Ruslan; Beta, A. Rivai (Universitas Pahlawan Tuanku Tambusai, 2025)
Digital technology is currently growing and affecting almost all lines of modern human life, including in sociocultural communication. The shift in the use of technology from analog to digital is intended to make everything easier, more practical, faster and more effective. This paper aims to examine what the influence of digital technology is in the transformation of sociocultural communication where this sociocultural tradition includes customs, culture, religion, language, and social strata. The research method chosen is qualitative with literature review data collection to collect data and information that provides an overview of current phenomena in sociocultural communication. This research is expected to provide knowledge about current digital technology products with their positive uses. Researchers also explain the negative effects if digital technology is not utilized wisely.